Intrusion detection system and technology of layered wireless sensor network based on Agent - Genjian Yu; Kunpeng Weng (Institute of Advanced Engineering and Science, 2013)
The intrusion detection system and technology of classified layered-wireless sensor network was able to meet the high safety requirements of wireless sensor network, it is urgent for us to improve the identification and generalization of detection system about characters of intrusion. In this paper, we design an intelligent intrusion detection system which realize intelligence, the effective and direct way was to add the methods, and it was used for identification and generalization of intrusion characters to the Agent function of intrusion detection. It could obtain credible judgment by updating and examining the database for the actions which the general misuse detection or anomaly detection were not sure if the intrusion was formed. DOI: http://dx.doi.org/10.11591/telkomnika.v11i8.2347